THE REPRESENTATION OF NOBITA WEAKNESS, IN DORAEMON STAND BY ME FILM - Astri Indriana Octavita (Wanastra: Jurnal Bahasa dan Sastra, 2020)
Literature intended for children is a literary work that contains the world of children, which is much related to the system of language and signs, which are used in accordance with the level of intellectual and emotional development of children. Anime 2112 Nen Doraemon Stand By Me is the work of director Yonetani Yoshimoto with a duration of about 1.5 hours. Doraemon is a cat robot that was mass produced by a factory in 2112. This study aims to obtain information about: portrayal of manga characters Doraemon's special story, namely Doraemon Stand By Me. The story in this anime is interesting to the writer because the author found a sign in the form of a marker (signifier) from the figure of Nobita. Nobita which shows the existence of several signs that refer to his representation. By using qualitative methods and accompanied by semiotic theory and representation of Barthes, as a research scalpel, the researcher intends to examine the representations of Nobita, Doraemon's best friend. The limitation of the problem in this study focused on the sign of Nobita's figure by analyzing the building elements, namely the element of narrative structure.Keywords: representation, semiotic, sign,  film, doraemon